Cover Image, Volume 87, Issue 4. (5th September 2017) - Battelino, Tadej; Rasmussen, Michael Højby; De Schepper, Jean; Zuckerman‐Levin, Nehama; Gucev, Zoran; Sävendahl, Lars; ,
Abstract : The cover image, by Tadej Battelino et al., is based on the Original Article Somapacitan, a once‐weekly reversible albumin‐binding GH derivative, in children with GH deficiency: A randomized dose‐escalation trial, DOI:10.1111/cen.13409 .